Tuning the photocatalytic selectivity of TiO2 anatase nanoplates by altering the exposed crystal facets content - Sofianou, Maria; Psycharis, V.; Boukos, N.; Vaimakis, T.; Yu, J.; Dillert, R.; Bahnemann, D.; Trapalis, C. (Elsevier BV, 2013)
TiO2 anatase nanoplates were fabricated by a solvothermal method using titanium isopropoxide as a titanium precursor and HF as a capping agent in order to enhance the formation of the {001} crystal facets of the anatase crystal. Two different surface modification procedures were applied in order to remove the adsorbed fluoride anions on the {001} crystal facets of the nanoplates. The first procedure was by calcining the as-prepared TiO2 anatase nanoplates up to 600°C and the second one was by washing them with a NaOH aqueous solution. Importantly, the surface modification procedure leads to the formation of two different morphologies of the TiO2 anatase nanoplates which exhibited tunable photocatalytic selectivity in air pollutants purification. The calcined nanoplates became larger and their {101} crystal facets expanded by shrinking the {001} crystal facets. In contrast the washed nanoplates maintained their shape which was formed by the solvothermal method. All samples that were calcined or washed, exhibited high photonic efficiency for air pollutants oxidation. The calcined TiO2 anatase nanoplates exhibited the best photocatalytic activity in oxidizing the NO gas to NO2 and NO3- whereas the washed TiO2 anatase nanoplates, preserving the initial morphology, exhibited the best photocatalytic activity in decomposing acetaldehyde. The dominant exposed {101} or {001} crystal facets of the TiO2 anatase nanoplates is the key factor in tuning the adsorption selectivity of the air pollutants. © 2013 Elsevier B.V.